A new Liopropoma sea bass (Serranidae, Epinephelinae, Liopropomini) from deep reefs off Curaçao, southern Caribbean, with comments on depth distributions of western Atlantic liopropomins - Baldwin, Carole C. (Pensoft Publishers, 2014)
Abstract. Collecting reef-fish specimens using a manned submersible diving to 300 m off Curaçao, southern Caribbean, is resulting in the discovery of numerous new fish species. The new Liopropoma sea bass described here differs from other western Atlantic members of the genus in having VIII, 13 dorsal-fin rays; a moderately indented dorsal-fin margin; a yellow-orange stripe along the entire upper lip; a series of approximately 13 white, chevron-shaped markings on the ventral portion of the trunk; and a reddish-black blotch on the tip of the lower caudal-fin lobe. The new species, with predominantly yellow body and fins, closely resembles the other two “golden basses” found together with it at Curaçao: L. aberrans and L. olneyi. It also shares morphological features with the other western Atlantic liopropomin genus, Bathyanthias. Preliminary phylogenetic data suggest that western Atlantic liopropomins, including Bathyanthias, are monophyletic with respect to Indo-Pacific Liopropoma, and that Bathyanthias is nested within Liopropoma, indicating a need for further study of the generic limits of Liopropoma. The phylogenetic data also suggest that western Atlantic liopropomins comprise three monophyletic clades that have overlapping depth distributions but different depth maxima (3–135 m, 30–150 m, 133–411 m). The new species has the deepest depth range (182–241 m) of any known western Atlantic Liopropoma species. Both allopatric and depth-mediated ecological speciation may have contributed to the evolution of western Atlantic Liopropomini.